Structure of the Amended Book VI of the Code of Canon Law of 1983 - Saj, Marek (Prawo Kanoniczne, 2022)
With the Apostolic Constitution Pascite gregem in 2021 pope Francis promulgated the amended Book of the Code of Canon Law of 1983. It concerns penal sanctions in the Latin Church and it came into force on 8th December last year. This concise analysis presents the Book with regard to its new structure. Attention has been turned on the names of particular parts, titles and chapters and also on the changes regarding the method of numbering of specific canons and "migration" of its content between canons. Nevertheless, we refrain from analysis of the purpose of the conducted changes. Thus, we offer strictly technical approach on the reformed Canon Book, which allows to show the vast range of the amendment introduced.